Which factors determine treatment choices in patients with advanced kidney failure? a protocol for a co-productive, mixed methods study - Gareth Roberts; Gail Williams; James A Chess; Teri Howells; Leah Mc Laughlin; Joanna M Charles; D J Dallimore (BMJ Open)
Introduction Kidney disease is common, affecting up to 1 in 10 of the adult population, and the numbers are expected to rise over the next decade. There are three main treatments that are available to patients with kidney disease: transplantation, dialysis and supportive care without dialysis. Dialysis can occur in a dialysis unit or in a person’s home, but unit-based dialysis remains the most common initial treatment for patients in Wales. This is a cause for concern as most studies suggest that it is associated with the lowest quality of life and the highest mortality, and is a more expensive treatment option.This study aims to identify the factors that lead to patients choosing unit-based haemodialysis rather than home-based dialysis with a view to informing future changes in patient education and service commissioning in Wales. A secondary aim is to determine if the co-production of research leads to more sustainable services.Methods and analysis This mixed-method study taking place between October 2018 and September 2020 will use a sequential explanatory design whereby the descriptive quantitative cross-sectional analysis of linked health and administrative data sets inform qualitative data collection from patients, carers and health and care professionals. Qualitative findings will be used to interpret or explain quantitative descriptive results. Additional strands to the study include a review of materials and education provided to patients and an economic review of treatment modalities.Ethics and dissemination The study will be conducted in accordance with the principles expressed in the Declaration of Helsinki. It has full approval from Health and Care Research Wales Research Ethics Committee #5. As a co-productive study involving patients, clinicians, third sector partners and academics, findings from this study will be shared on a continual basis. Study results will be published in peer-reviewed journals and presented at national and international conferences.